All-in-one self-powered flexible microsystems based on triboelectric nanogenerators. (May 2018) - Zhang, Xiao-Sheng; Han, Mengdi; Kim, Beomjoon; Bao, Jing-Fu; Brugger, Juergen; Zhang, Haixia
Abstract: Wearable electronics experienced a blooming prosperity in the past decade due to their trend of miniaturization and smart functions integration, and the appealing intrinsic physical properties, such as flexibility, stretchability, and conformability. Although wearable electronics play an important role in modern society, either as sensing devices for information collection or as mobile terminates for data exchange, further wider applications essentially require overcoming the restriction of traditional rigid, unsustainable power sources, thereby promoting the favorable properties of stability, high-output, maintenance-free, flexibility and also stretchability for the most sophisticated wearable electronics. Moreover, an attractive future vision of the development of wearable electronics is to integrate discrete components, including but not limited to sensors, actuators, integrated circuits and power sources, in order to realize self-powered flexible microsystems. Quantitative comparison and qualitative analysis prove that emerging triboelectric nanogenerators (TENGs) represents a powerful and promising approach to address the challenges above. TENGs, which scavenge the mechanical energy from ambient environment based on the combination of contact electrification and electrostatic induction, have been demonstrated to be a robust power source for a diverse set of applications. Furthermore, a new concept of self-powered system exploits the electricity generated by TENG to directly provide the power supply to other functional parts of the system. An additional option of self-powered system involves utilizing the quantitative relation between electrical signals and environmental changes to realize active sensors. Here, this paper reviews the feasibility of "all-in-one" self-powered flexible microsystems by introducing the technology of TENG around the following major categories: working principles, advanced materials, TENG-based active sensors, TENG-powered actuators, and integrated microsystems. Graphical abstract: fx1 Highlights: Propose and illustrate a concept of "All-in-One" self-powered flexible microsystems. Review and compare five common technologies for ambient energy harvesting. Summarize the recent progress of triboelectric nanogenerators in four aspects. Emphasize the rapid growth of triboelectric nanogenerators for wearable applications.